Linkages between the Sustainable Development Goals and health in Somalia - Rage Adem; Hassan W. Nor; Mohamed M. Fuje; Abdinur H. Mohamed; Tobias Alfvén; Rhoda K. Wanyenze; Ahmed Y. Guled; Mohamed M. Biday; Nina Viberg; Daniel Helldén (BMC, 2024)
Abstract Background The Sustainable Development Goals (SDGs) adopted in 2015 compromises 17 universal and indivisible goals for sustainable development, however the interactions between the SDGs in Somalia is not known which is vital for understanding potential synergies and trad-offs between the SDGs. Hence, this study aims to identify and classify the linkages between the SDGs with a focus on health and well-being (SDG 3) in Somalia. Methods Following the SDG Synergies approach, 35 leading experts from the public and private sectors as well as academia and civil society gathered for a 2-day workshop in Mogadishu and scored the interactions between the individual SDGs on a seven point-scale from − 3 to + 3. From this, a cross-impact matrix was created, and network models were used to showcase the direct and indirect interactions between the SDGs with a focus on SDG 3 (good health and well-being). Results Many promoting and a few restricting interactions between the different SDGs were found. Overall, SDG 16 (peace, justice, and strong institutions) influenced the other SDGs the most. When second-order interactions were considered, progress on SDG 16 (peace, justice, and strong institutions) showed the largest positive impact on SDG 3 (good health and well-being). SDG 3 (good health and well-being) was heavily influenced by progress on other SDGs in Somalia and making progress on SDG 3 (good health and well-being) positively influenced progress on all other SDGs. Conclusion The findings revealed that in Somalia, the interactions between the SDGs are mostly synergistic and that SDG 16 (peace, justice, and strong institutions) has a strong influence on progress on other SDGs as well as progress on SDG 3 (good health and well-being). This study highlights the need for a multisectoral strategy to accelerate progress on the SDGs in Somalia in general, and particularly SDG 3 (good health and well-being).